Cardiac Adaptations Molecular Mechanisms - Ostadal, Bohuslav.; Dhalla, Naranjan S. (Advances in Biochemistry in Health and Disease ;, 2013)
The processes of adaptation and maladaptation play an important role in the pathogeny of serious cardiovascular diseases, such as hypertension, valvular diseases, congenital heart disease, myocardial infarction and different cardiomyopathies as well as during adaptation to exercise and high altitude hypoxia. This volume incorporates the rapidly developing basic and clinically relevant information on adaptive mechanisms, thereby contributing to the better understanding of possible prevention and therapy of life-threatening cardiovascular diseases. The first section of this volume focuses on developmental aspects of cardiac adaptation, including chapters on comparative and molecular aspects of cardiac development, prenatal and postnatal developments, coronary vascular development, and ontogenetic adaptation to hypoxia, as well as cardiac and arterial adaptation during aging. The second section is devoted to cardiac adaptations to overload on the heart, centered around the mechanisms of cardiac hypertrophy due to pressure overload, volume overload, exercise, gender difference, high altitude, and different pathological situations. The third section of this volume highlights the roles of sympathetic nervous system with respect to ł-adrenoceptor and ø-adrenoceptor mechanisms in the development of cardiac hypertrophy. Cardiac Adaptations will be of great value to cardiovascular investigators, who will find this book highly useful in their cardiovascular studies for finding solutions in diverse pathological conditions; it will also appeal to students, fellows, scientists, and clinicians interested in cardiovascular abnormalities.